2017
DOI: 10.1002/2017ja023886
|View full text |Cite
|
Sign up to set email alerts
|

Annual and interannual variations in global 6.5DWs from 20 to 110 km during 2002–2016 observed by TIMED/SABER

Abstract: Using version 2.0 of the TIMED/SABER kinetic temperature data, we have conducted a study on the annual and interannual variations of 6.5DWs at 20–110 km, from 52°S to 52°N for 2002–2016. First, we obtained global annual variations in the spectral power and amplitudes of 6.5DWs. We found that strong wave amplitudes emerged from 25°S/N to 52°S/N and peaked in the altitudes of the stratosphere, mesosphere, and the lower thermosphere. The annual variations in the 6.5DWs are similar in both hemispheres but differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 60 publications
5
48
0
Order By: Relevance
“…The occurrence date and the period of all the Q6DWs during 2003–2017 are recorded, and their statistical results are shown in Figures and . Figure indicates that this planetary wave usually appears in April–May and August–October, exhibiting a quasi‐semiannual oscillation, which is consistent with previous study (Huang et al, ; Jiang et al, ; Lieberman et al, ; Liu et al, ; Talaat et al, ; Wu et al, ). Besides, we noticed that there are three Q6DW events during February, which are slightly more than those that occur in January (one event) and March (two events).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The occurrence date and the period of all the Q6DWs during 2003–2017 are recorded, and their statistical results are shown in Figures and . Figure indicates that this planetary wave usually appears in April–May and August–October, exhibiting a quasi‐semiannual oscillation, which is consistent with previous study (Huang et al, ; Jiang et al, ; Lieberman et al, ; Liu et al, ; Talaat et al, ; Wu et al, ). Besides, we noticed that there are three Q6DW events during February, which are slightly more than those that occur in January (one event) and March (two events).…”
Section: Resultssupporting
confidence: 91%
“…Our statistical results also show the Q6DW peaks during April/May and September/October, which exhibit a quasi‐semiannual oscillation with a period of not exactly 6 months as shown by Huang et al (). Additionally, we found that the Q6DW also shows a relatively high occurrence rate during February, the reason of which is still unclear.…”
Section: Discussionsupporting
confidence: 86%
“…It is surprising to see that TAO in the 5DW amplitudes is as important as the commonly recognized AO and SAO at MLT region. Using the SABER temperature measurements averaged in the altitude range from 80 to 90 km, Huang et al () found that the 6.5‐day wave has a strong TAO in the latitudinal range from 40°N to 52°N, which is consistent with our results. They stated that SAO is stronger than AO at 80 to 90 km in the latitudinal range from 30°N to 52°N.…”
Section: Latitudinal Seasonal and Interannual Variationssupporting
confidence: 92%
“…Note that oscillations with periods between 4 and 7 days are considered as the 5DWs in this study. For satellite observations, the two‐dimensional fast Fourier transform is an effective way to obtain spectral analysis (e.g., Huang et al, ; Merzlyakov & Pancheva, ) and is adopted in this study. Figure a presents a moving periodogram of the zonal wind at 90 km in the period of 20 April to 20 May 2012 over MH.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation